2003
DOI: 10.1093/jn/133.6.1853
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Bioavailability Largely Depends on Its Metabolism by the Gut Microflora in Rats

Abstract: Chlorogenic acid, the ester of caffeic acid with quinic acid, is one of the most abundant polyphenols in the human diet with coffee, fruits and vegetables as its major sources. Its antioxidant and anticarcinogenic properties have been well established in animal studies. However, little is known about its gut absorption and metabolism. In the present work, four groups of rats (n = 8) were fed a diet supplemented with chlorogenic, caffeic or quinic acids (250 micromol/d) or an unsupplemented diet for 8 d. Parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
401
1
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(437 citation statements)
references
References 54 publications
16
401
1
19
Order By: Relevance
“…Strongest correlations are explained by metabolic filiations such as for chlorogenic acid and caffeic acid (hydrolysis) (Gonthier et al, 2003), gallic acid and 4-O-methylgallic acid, quercetin and isorhamnetin (methylation), enterolactone and enterodiol (hydrolysis and reduction) (Borriello et al, 1985). We also reported in a previous study the excretion of phloretin after consumption of citrus juice and suggested that phloretin is a metabolite of naringenin formed by reductive opening of the heterocycle (Ito et al, 2005).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Strongest correlations are explained by metabolic filiations such as for chlorogenic acid and caffeic acid (hydrolysis) (Gonthier et al, 2003), gallic acid and 4-O-methylgallic acid, quercetin and isorhamnetin (methylation), enterolactone and enterodiol (hydrolysis and reduction) (Borriello et al, 1985). We also reported in a previous study the excretion of phloretin after consumption of citrus juice and suggested that phloretin is a metabolite of naringenin formed by reductive opening of the heterocycle (Ito et al, 2005).…”
Section: Discussionmentioning
confidence: 63%
“…This explains the high correlation observed here between these two compounds. mCoumaric acid is also weakly correlated to caffeic acid and is formed by microbial dehydroxylation of the latter in the colon (Gonthier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers affirm that chlorogenic acid is the most common phenolic compound in food and its main sources are fruits, coffee, vegetables, cereals and spices (GONTHIER et al, 2003;CLIFFORD, 1999). In this work, spices were screened for the presence of hydroxycinnamic acids, but these polyphenols were detected only in basil, chives, oregano and rosemary.…”
Section: And 5)mentioning
confidence: 95%
“…Furthermore, the good percentage of p-coumaric acid found in the organically and conventionally produced Annurca could be significant since this biomolecule has received a lot of attention in the recent years for its anti inflammatory in vivo properties [23]. Moreover, the high level of chlorogenic acid, observed mainly in organic fruits is of great meaning as in vivo studies have demonstrated the antioxidant and anticarcinogenic properties of this biomolecule, in general inefficiently absorbed in small intestine, but capable of providing higher yields of microbial metabolites, active compounds responsible for the biological properties attributed to dietary polyphenols [24][25]. The characterization of conventional and organic apple aimed at the identification of compounds developed by plant tissues as part of their defence mechanism was carried out by Lucarini et al [26], which indicated higher levels of both polyphenols and specific phenolic acids, as p-coumaric and caffeic acid, in organically than in conventionally produced apples.…”
Section: Hplc Analysismentioning
confidence: 99%